An Assessment of Neighborhood Safety Concerns in South African Peripheral Urban Communities - Ndamase, Siwakhe; Obioha, Emeka E (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2024)
Given the current crime situation in South Africa, this present study investigates the nature of residents' neighborhood safety concerns, the social and demographic determinants, and how to ameliorate the situation in peripheral urban communities. The study used a sample of 110 participants drawn through a stratified random sampling technique from the adult population of peripheral urban communities of Libode and Ngqeleni in South Africa. The study adopted a mixed method approach, dominated by a quantitative approach, where a survey instrument (Questionnaire) was mainly used to collect data. The study found youth unemployment in the area, night walks, absence of organized neighborhood watch, lack of police visibility, and abandoned houses as major critical safety concerns in the communities' neighborhoods. Notably, most residents expressed safety concerns, but higher neighborhood safety concerns were significantly associated with marriage, lower number of years living in the neighborhood, and femaleness. On the other hand, even though more urbanized locations, being old (over 60 years), being employed, salaried, and of high school level are associated with higher safety concerns in the neighborhood, but not at a statistically significant level. While residents believe that more job creation and community participation in organized neighborhood watch could be a source of solution, this study's major implication lies in the importance of addressing these critical factors in the relevant policies and practices in the country.